Pengaruh SPIP dan Software Aplikasi SIMDA BMD Terhadap Kualitas Penatausahaan Aset Tetap (Studi Kasus Pada Pemerintah Kota Bandung) - Chandra Artedi; Rendra Trisyanto Surya (Indonesian Accounting Research Journal, 2022)
This research was conducted to find out how much influence SPIP and SIMDA BMD and the use of SIMDA BMD Application Software had on the quality of Fixed Assets Administration and how the fixed asset administration system was implemented at the Bandung City Government. Problems with fixed assets, especially asset administration, are still an obstacle for the Bandung City Government. In this study using descriptive quantitative research with the population of this study were 60 OPD in the Bandung City Government with a sample consisting of 30 namely the Regional Secretariat, Regional Inspectorate, Service, Agency, and Civil Service Units and Firefighters and OPD who using the SIMDA BMD application onlythe data subject is the data used in this research. The data sources used are primary data by distributing questionnaires and interviews. Results Based on this research, the overall fixed asset administration system is carried out with the existing provisions, the assessment of the fixed asset administration process is the bookkeeping, inventory, and reporting processes. Partially it has a significant influence from SPIP on the quality of Fixed Asset Administration with a strong relationship and SIMDA BMD Application Software with a fairly strong relationship. While simultaneously also has a significant effect.